2022
DOI: 10.1186/s12929-022-00856-5
|View full text |Cite
|
Sign up to set email alerts
|

Treating ARID1A mutated cancers by harnessing synthetic lethality and DNA damage response

Abstract: Chromatin remodeling is an essential cellular process for organizing chromatin structure into either open or close configuration at specific chromatin locations by orchestrating and modifying histone complexes. This task is responsible for fundamental cell physiology including transcription, DNA replication, methylation, and damage repair. Aberrations in this activity have emerged as epigenomic mechanisms in cancer development that increase tumor clonal fitness and adaptability amidst various selection pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 124 publications
(129 reference statements)
2
52
1
1
Order By: Relevance
“…Recent advances, including CRISPR/Cas9-based gene editing, have made possible systematic screens for synthetic lethal targets in human cancers harboring mutations of tumor suppressor, such as ARID1A. Ever since the discovery as a tumor suppressor for ARID1A, synthetic lethal phenotypes have been uncovered in ARID1A-deficient cells when treated with PARP inhibitors, ATR inhibitors, EZH2 inhibitors, and other emerging agents [ 13 ].…”
Section: Arid1a: Synthetic Lethality and Beyondmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances, including CRISPR/Cas9-based gene editing, have made possible systematic screens for synthetic lethal targets in human cancers harboring mutations of tumor suppressor, such as ARID1A. Ever since the discovery as a tumor suppressor for ARID1A, synthetic lethal phenotypes have been uncovered in ARID1A-deficient cells when treated with PARP inhibitors, ATR inhibitors, EZH2 inhibitors, and other emerging agents [ 13 ].…”
Section: Arid1a: Synthetic Lethality and Beyondmentioning
confidence: 99%
“…Given the emerging roles of ARID1A in the DNA damage response [ 13 ], accumulating evidence has enhanced our understanding of the biological role of ARID1A, offering new mechanisms for synthetic lethality-based targeting of ARID1A-inactivated cancers, such as inhibition of PARP [ 71 , 72 ] and ATR [ 73 ]. Recently, Wang et al reported that ARID1A-mutated/deficient tumors exhibited high expression of Chk2, a DNA damage checkpoint kinase downstream of ATM, through modulating autoubiquitination of the E3-ligase RNF8 and thereby reducing RNF8-mediated Chk2 degradation.…”
Section: Arid1a-deficiency: An Immune-metabolic Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Different subunits are associated with different tumors: for example, SMARC1 loss is seen in atypical teratoid/rhabdoid tumors (ATRTs), among others [380,381], whereas AIRD1A loss has been described in endometrioid EC (~40%), endometrioid (~30%), clear-cell (46-57%) OCs, etc., with up to ~20% of all human cancers harboring AIRD1A-inactivating mutations [337,372,[382][383][384][385]. In addition, the loss of ARID1A has been demonstrated in patient samples with atypical endometriotic lesions contiguous to clear-cell OC, raising the possibility that the loss of ARID1A may contribute to an early cancer-promoting event in endometriosis that leads to clear-cell OC [337].…”
Section: Arid1amentioning
confidence: 99%
“…Additionally, in ~13% of BCs, there is mostly a loss of heterozygosity of ARID1A, resulting in reduced protein expression and a more aggressive cancer phenotype [386]. In various tumors, ARID1A loss is mainly due to ARID1A promoter hypermethylation, but it also can be due to inactivating mutations or in-frame insertions/deletions [382,386]. In some cases, post-translational changes lead to the loss of the ARID1A protein.…”
Section: Arid1amentioning
confidence: 99%